Strategi Penafkahan Keluarga Nelayan Perspektif Fikih Mazhab Syafi’i: Studi Living Law Di Desa Puger Kulon - Falyafil, Ivan Zakariya; Aisyah, Aisyah (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the livelihood strategies of fishermen families in Puger Kulon from the perspective of Shafi’i Islamic jurisprudence using a living law approach. This research employs a descriptive analytical qualitative field method through in-depth interviews, observation, and documentation involving fishermen families. The analysis uses Eugen Ehrlich’s living law theory to examine the relationship between Shafi’i jurisprudence as law in books and fishermen’s livelihood practices as law in action. The findings show that fishermen families in Puger Kulon develop adaptive livelihood strategies, such as accumulating income during abundant seasons, delegating financial management to wives, and adjusting livelihood patterns during lean seasons. These strategies emerge as responses to unstable income. Such practices result from the interaction between value-oriented rationality to obey religious teachings and instrumental rationality to survive economically. This study concludes that fishermen’s livelihood practices can be understood as a form of living fiqh, namely Islamic law that lives and operates within social reality. Although technically different from textual provisions of Shafi’i jurisprudence, these practices remain substantively valid because they fulfill the objectives of maqashid al-sharia, particularly in protecting life and sustaining family welfare. This study contributes to the discourse on Islamic family law by conceptualizing fishermen's livelihood practices as living fiqh within fluctuating economic contexts.